The forensic pathological analysis of sport-related sudden cardiac death in Southern China - Yeda Wu; Mei Ai; Adham Sameer A. Bardeesi; Liyong Zhang; Qiuping Wu; Kun Yin; Jingjing Zheng; Da Zheng; Lei Huang; Lunwu Xu; Jianding Cheng (Oxford University Press, 2020)
Studies regarding sport-related sudden cardiac death (SCD) mainly focus on competitive athletes; similar data are rare in the general population, especially in China. We conducted a retrospective study (from September 1998 to August 2013) to investigate the aetiological distribution and epidemiological features of sport-related SCD in Southern China. Selections of cases are based on details, and two subgroups were established: one was the sport-related SCD group, and the other was the disease-free accident victims group which was matched with the sport-related SCD group in gender, age and year of death. Among the 3770 sudden-death cases, 1656 cases were SCD cases. A total of 65 cases (57 males) out of 1 656 SCD cases were sport-related. The age range of the 65 sport-related SCD cases was from 12 to 68 years old with a mean (35.92 ± 14.23) years old. Only two of these cases were competitive athletes. The most common circumstances of the 65 sport-related SCD cases were heavy physical labour (46.15%) and running (30.77%). The three leading forensic diagnoses were the coronary atherosclerotic disease (CAD, 28 cases), cardiomyopathy (CM, 14 cases) and sudden unexplained death (7 cases). CM was the most common forensic diagnosis in those ≤35 years old, while CAD was the most common one in those >35 years old. Left anterior descending in which atherosclerotic plaques was most commonly found was the principal artery branch associated with sport-related SCD. There was a statistically significant difference in the weight of hearts between the 65 sport-related SCD cases and 65 diseases-free accidental cases. This study highlights the need to attract public attention to sport-related SCD and to issue a prevention strategy to the public, and to make the SCD-related genetic sequencing a routine tool in both forensic pathological examination and clinic screening.